Structural and spectroscopic characterizations of new Cd1−3xNd2x□xMoO4 scheelite-type molybdates with vacancies as potential optical materials. Issue 16 (19th March 2015) - Guzik, M.; Tomaszewicz, E.; Guyot, Y.; Legendziewicz, J.; Boulon, G.
Abstract : Spectroscopic analysis of Nd 3+ in Cd1−3 x Nd2 x □ x MoO4 points out two non-equivalent symmetry sites depending on the location of the □ vacancies. Both short lifetimes and high emission intensities suggest that the compounds could be especially promising for an ultra-short pulse laser generation. Abstract : The necessity to develop new laser materials of tungstates and molybdates is our motivation to study a new family of molybdates activated by Nd 3+ ions, which crystallizes in the scheelite-type structure (the tetragonal symmetry, the space group I 41 / a ). A series of Cd1−3 x Nd2 x □ x MoO4 stable solid solutions with concentration of Nd 3+ ions from 0.1 mol% to 66.67 mol% with respect to Cd 2+ ions were successfully synthesized by a high-temperature annealing, using CdMoO4 and Nd2 (MoO4 )3 as the starting materials. Structural and spectroscopic characterizations of Nd 3+ substituting Cd 2+ ions were carried out. The substitution of divalent Cd 2+ by trivalent Nd 3+ cations leads to the formation of cationic vacancies in the framework (which are denoted in the chemical formula as □). The Nd 3+ ions in this matrix occupy two non-equivalent symmetry sites depending on the location of these vacancies. Concentration of vacancies depends essentially on the composition of initial CdMoO4 –Nd2 (MoO4 )3 mixtures. The SEM analysis of crystal morphology reveals high homogeneity of the nearly-spherical shaped products with an average grain size of about 1–10 μm. Optical analysis and the laser parameters suggest that Cd1−3 x Nd2 x □ x MoO4 can be considered as a potential laser material. Both the values of the absorption cross-section and the strong emission of the 4 F3/2 → 4 I11/2 laser channel of Nd 3+ recorded under LED source excitation or OPO laser pumping, as well as the radiative lifetimes of NIR luminescence, are appropriate for potential applications of this optical material as a solid state laser.